2015
DOI: 10.1038/ncomms7532
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical integrated stress response enhancement protects oligodendrocytes and provides a potential multiple sclerosis therapeutic

Abstract: Oligodendrocyte death contributes to the pathogenesis of the inflammatory demyelinating disease multiple sclerosis (MS). Nevertheless, current MS therapies are mainly immunomodulatory and have demonstrated limited ability to inhibit MS progression. Protection of oligodendrocytes is therefore a desirable strategy for alleviating disease. Here we demonstrate that enhancement of the integrated stress response using the FDA-approved drug guanabenz increases oligodendrocyte survival in culture and prevents hypomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 57 publications
6
98
0
Order By: Relevance
“…One study found that, on average, ϳ2 M guanabenz can be detected in the brains of mice at 2 to 4 h postinjection (28), which corresponds to the concentration that we found to inhibit Toxoplasma proliferation in vitro (Fig. 1A).…”
Section: Discussionsupporting
confidence: 67%
“…One study found that, on average, ϳ2 M guanabenz can be detected in the brains of mice at 2 to 4 h postinjection (28), which corresponds to the concentration that we found to inhibit Toxoplasma proliferation in vitro (Fig. 1A).…”
Section: Discussionsupporting
confidence: 67%
“…Targeting the same pathway is also beneficial in a model of multiple sclerosis. Enhancement of PERK signaling by a genetic approach or sustained eIF2α phosphorylation with the GADD34 inhibitor guanabenz protects oligodendrocytes from death induced by EAE (Tsaytler et al, 2011; Lin et al, 2013; Way et al, 2015). Recently, Sephin1, a more specific GADD34 inhibitor, has been shown to largely prevent the motor, morphological, and molecular defects of S63del mice (Das et al, 2015).…”
Section: Erqc and Charcot-marie-tooth (Cmt) Neuropathiesmentioning
confidence: 99%
“…These target-dependent toxicities include pancreatic injury as well as behavioral inflexibility, which is a hallmark of autism spectrum disorders [74,75]. Inhibition of eIF2α phosphorylation may also exacerbate motor neuron disease [76,77]. …”
Section: Expert Opinionmentioning
confidence: 99%